Temporal stability of induction vectors from Antarctic Peninsula, AIA INTERMAGNET observatory - Sanaka, S.; Neska, A. (Ukrainian Antarctic Journal, 2023)
Induction vectors represent geomagnetic transfer functions used in magnetotellurics and related passive electromagnetic sounding methods in geophysics. They are obtained from the measurements of geomagnetic variation and carry information on the distribution of local and regional electric resistivity in the subsurface, which can be interpreted in terms of geology and tectonics. The underlying concept of their interpretation works properly if the so-called far-field condition is fulfilled, i.e., if certain assumptions on the geometry of utilized natural electromagnetic source fields are met. The magnetotelluric practitioner expects problems in the regions where the electromagnetic variations originate to a high extent from ionospheric currents as sources. Due to the polar (or auroral) electrojets, this skepticism towards the electromagnetic far-field methods clearly applies to the high latitudes, polar regions, and auroral zones. In the present study, the investigation focuses on the extent to which problems typical for the auroral electrojet sources occur in the geomagnetic variation data from the Argentine Islands INTERMAGNET observatory (AIA) located at the Ukrainian Antarctic Akademik Vernadsky station. Induction vectors from one month of AIA variation data measured in the normal framework of the INTERMAGNET observatory are analysed for their stability over both period and time, where a time resolution of one day allows for the detection of changes originating from the source signals instead of from subsurface resistivity distribution. The outcomes from AIA are compared to the corresponding ones of two northern hemisphere stations which belong to the International Monitor for Auroral Geomagnetic Effects (IMAGE) network, located in Finland and Poland. Results show that AIA induction vectors do not exhibit the problems expected in the high latitudes; their time stability is very similar to that of stations at a comparable but opposite geomagnetic latitude of 50 degrees, which corresponds geographically to mid-latitudes in Europe. A further outcome of this study is that some slight, occasional changes in induction vectors can be attributed to increased geomagnetic activity because they are correlated to the planetary diurnal Ap index.